2012
DOI: 10.1161/strokeaha.111.632265
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to Axonopathy in Necrotic and Non-Necrotic Perinatal White Matter Injury

Abstract: Background and Purpose White matter injury (WMI) is the leading cause of brain injury in preterm survivors and results in myelination failure. Although axonal degeneration occurs in necrotic lesions, the role of axonopathy in myelination failure remains controversial for diffuse non-necrotic WMI, which is currently the major form of WMI. We determined the burden of axonopathy in diffuse lesions. Methods We analyzed WMI in a preterm fetal sheep model of global cerebral ischemia that replicates the relative bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…During the chronic phase of WMI from this same fetal sheep preparation [46] and human [54], microscopic foci of necrosis were observed that were rich in microglia, but lacked astrocytes or axons. However, no significant axonal degeneration, axonal loss or shift in the distribution of axon calibers was observed by quantitative electron microscopy studies in preterm fetal sheep [53]. Hence, the contribution of microscopic necrosis to axonal loss with secondary myelination failure appears to be low, but there is a need for further human neuropathological studies with sensitive markers of axonal injury that are applied to cases of diffuse WMI that lack necrosis.…”
Section: Mri-guided Ultrastructural Studies Of Axonal Degeneration Inmentioning
confidence: 97%
See 2 more Smart Citations
“…During the chronic phase of WMI from this same fetal sheep preparation [46] and human [54], microscopic foci of necrosis were observed that were rich in microglia, but lacked astrocytes or axons. However, no significant axonal degeneration, axonal loss or shift in the distribution of axon calibers was observed by quantitative electron microscopy studies in preterm fetal sheep [53]. Hence, the contribution of microscopic necrosis to axonal loss with secondary myelination failure appears to be low, but there is a need for further human neuropathological studies with sensitive markers of axonal injury that are applied to cases of diffuse WMI that lack necrosis.…”
Section: Mri-guided Ultrastructural Studies Of Axonal Degeneration Inmentioning
confidence: 97%
“…This shortcoming, for example, limits the relevance of rodent hypoxia-ischemia models for the study of myelination disturbances associated with chronic human WMI. Necrotic injury to cerebral gray matter contributes substantially to neuro-axonal degeneration as a cause of dysmyelination, which is not a prominent feature of WMI in either fetal sheep [53] or contemporary human cases of WMI [54]. The basis for this difference in susceptibility to gray matter injury in rodents relative to sheep and humans is likely to be multifactorial.…”
Section: Advantages and Disadvantages Of The Fetal Sheep To Model Wmimentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it is closely correlated with the relative vulnerability of late oligodendrocyte progenitors in rabbit, sheep, and human (11,12). Furthermore, in vitro, central premyelinating axons are reported to be much more vulnerable to ischemic injury than adjacent myelinated axons or smaller axons that had not reached the stage of radial expansion (13), likely contributing to the high risk of axonopathy in necrotic periventricular white matter lesions (14).…”
Section: Mechanisms Of Perinatal Brain Injurymentioning
confidence: 99%
“…Disruption of early contact between the cortex and thalamus may also disrupt connectivity and lead to remodeling of cortical circuitry due to target deprivation-induced ("Wallerian") neurodegeneration (72). Nevertheless, although historical data demonstrate axonal injury within and around periventricular white matter necrosis (9), there does not appear to be significant axonal damage in nonnecrotic fetal ovine WMI (73). Similarly, in a postmortem cohort of preterm infants, axonal degeneration was only seen in necrotic foci, in association with microglial activation, but not in areas…”
Section: What Is the Link Between Cortical Maturation And Wmi?mentioning
confidence: 99%